1965
DOI: 10.1002/app.1965.070090408
|View full text |Cite
|
Sign up to set email alerts
|

Incremental modification of styrene‐butadiene rubber with tert‐nonyl mercaptan

Abstract: A model equation derived for the viscosity-average degree of polymerization (P.) for the incremental addition of modifiers, P, = K ( (exp{arzl] indicates a minimum should occur in a curve of P. versus conversion at which the increments are added, zl. Incremental addition of commercial tertdodecyl mercaptan in the laboratory to SBR recipes a t 5°C. showed effects contrary to those predicted by the model equation, but incremental addition experiments with tert-nonyl mercaptans resulted in a minimum in viscosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1968
1968
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…On the other hand, when t-nonyl mercaptan, which diffuses rapidly, was used, a marked advantage of using semicontinuous addition was observed. 18 Echevarria et al 19 developed a closedloop control strategy based on on-line gas chromatographic measurements of both monomer and CTA to obtain emulsion polymers of well-defined MWD. The control strategy was experimentally assessed, producing widely different MWDs in the styrene emulsion polymerization using carbon tetrachloride as CTA.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when t-nonyl mercaptan, which diffuses rapidly, was used, a marked advantage of using semicontinuous addition was observed. 18 Echevarria et al 19 developed a closedloop control strategy based on on-line gas chromatographic measurements of both monomer and CTA to obtain emulsion polymers of well-defined MWD. The control strategy was experimentally assessed, producing widely different MWDs in the styrene emulsion polymerization using carbon tetrachloride as CTA.…”
Section: Introductionmentioning
confidence: 99%
“…[exp ( a r~) -~I / [~x Y ( ' +~) I (1) where M o is the initial monomer, SO is the initial modifier concentration, r is the regulating index, a is the Mark-Houwink exponent, and X is the fractional conversion. A P , -r plot gives a concave curve, and eq.…”
Section: P = K ( M~/ S~) {mentioning
confidence: 99%
“…Equations (1) and (2) can be used to show that modifiers with high regulating indexes are needed for efficient modification of polymerizations terminated at low conversions. If a manyfold incremental modifier experiment is viewed as a sum of a consecutive series of short conversion intervals, than in manyfold addition modifiers with much higher regulating indexes are needed for efficient modification in comparison to the single addition control taken to the same final conversion.…”
Section: Model Equations and Simulated Calculationsmentioning
confidence: 99%
“…Uraneck and Burleigh. 8 studied the incremental addition of TDM and tert-nonyl mercaptan. For TDM it was found that MV and inherent viscosity were higher than the obtained when total CTA was initially added.…”
Section: Introductionmentioning
confidence: 99%